Stalin’s Repression Agaınst Kyrgyz Intellectuals - ERGESH KYZY, Aziza (Scientific Journal of Faculty of Theology, 2020)
Stalin’s repressions against Kyrgyz intellectuals began in the period of the Communist Bolshevik Party, which came to power after the October Revolution. Because during this period all local organizations had to obey the decisions of the corresponding party. The Communist Party, institutionalized in accordance with the theory of Marxism and Soviet ideology, was aimed at eliminating class differences in society. For this reason, in addition to the regions associated with the party, the rulers began to put pressure on rulers such as “feudal aristocrats”, “nationalists” and “religious people” who were considered colonial and bourgeois in the territory of Turkestan. Thus, the party sought to create a more efficient and exemplary socialist regime, getting rid of groups opposing its rule. In this regard, they continued the political practice, which they called “equality” between 1920-1950. The pressure, which they called the scrub motion in this process, reached its peak, especially in 1937-1938. In this context, Kyrgyz intellectuals were among the most vulnerable peoples. Most of these intellectuals were young people, educated before the October Revolution, members of noble families and who has different opinions. They were the first intellectuals of the Kyrgyz people, who for a long time could not fill their place. Since the late 1920s, the Kyrgyz intellectuals has been accused of becoming members of the so-called Social Turan Party, whose feelings of opposition have become stronger. For this reason, the Kyrgyz intellectuals was almost completely eliminated, and the future of the Kyrgyz people was struck by Stalinist ideas.